THE CALLOVIAN UNCONFORMITY AND THE OPHIOLITE OBDUCTION ONTO THE PELAGONIAN CARBONATE PLATFORM OF THE INTERNAL HELLENIDES - Scherreiks, R.; Meléndez, G.; Bouldagher-Fadel, M.; Fermeli, G.; Bosence, D. (Bulletin of the Geological Society of Greece, 2016)
The carbonate-platform-complex and the oceanic formations of the central Pelagonian zone of the Hellenides evolved in response to a sequence of plate tectonic episodes of ocean spreading, plate convergence and ophiolite obduction. The biostratigraphies of the carbonate platform and the oceanic successions, show that the Triassic-Early Jurassic platform was coeval with an ocean where pillow basalts and radiolarian cherts were being deposited. After convergence began during late Early- Jurassic - Middle Jurassic time, the oceanic leading edge of the Pelagonian plate was subducted beneath the leading edge of the oceanic, overriding plate. The platform subsided while a supra-subduction, volcanic-island-arc evolved. Biostratigraphic and geochemical evidence shows that the platform and the oceanic floor, temporarily became subaerially exposed during Callovian time. This “Callovian event” is suggested to have taken place as oceanic lithosphere first made compressional, tectonic contact with the carbonate platform, initiating a basal detachment fault, along which the platform was thrust upwards. The central Pelagonian zone became an extensive land area that was supplied with laterite from an ophiolite highland. A similar emergence of Vardar ophiolite most likely took place in the Guevgueli area. The Callovian emergence shows that the initial ophiolite obduction onto the platform took place about 25 million years before the final emplacement of the ophiolite during Valanginian time.